004 Mechanisms of nerve dysfunction in inflammatory neuropathies. Issue 6 (24th May 2018) - Garg, Nidhi; Park, Susanna B; Howells, James; Yiannikas, Con; Vucic, Steve; Noto, Yu-ichi; Krishnan, Arun V; Spies, Judith; Mathey, Emily K; Pollard, John D; Kiernan, Matthew C
Abstract : Introduction: Immune-mediated neuropathies are a cause of disability and an immense cost to the healthcare system. They include chronic inflammatory demyelinating polyneuropathy (CIDP), multifocal motor neuropathy (MMN) and the neuropathy associated with IgM antibodies against myelin-associated glycoprotein (MAG). CIDP is extremely heterogeneous with marked variability in treatment responsiveness. Patients with MMN often respond to treatment but progressive weakness and wasting typically ensues over time. No therapy has consistently proven effective in anti-MAG neuropathy. The present series of studies were undertaken to improve understanding of disease mechanisms in these neuropathies, a critical step before targeted treatment approaches can be developed. Methods: Patients fulfilling Peripheral Nerve Society criteria for CIDP or MMN and patients positive for anti-MAG IgM underwent comprehensive clinical assessments, neurophysiology, serological testing and structural assessments. Results: The patient cohort consisted of 80 patients (51 CIDP, 14 MMN, 15 MAG). 6% of CIDP patients tested positive for anti-neurofascin 155 (NF155) and 4% for anti-contactin 1 IgG4. Anti-NF155 neuropathy was characterised by diffuse nerve enlargement and an axonal excitability profile consistent with severe disruption of the paranodal seal. CIDP patients testing negative for IgG4 antibodies also demonstrated significant nerve enlargement compared with healthy subjects. Axonal excitability profiles differed in those with and without median nerve conduction block. MMN was characterised by patchy nerve enlargement, marked increases in super-excitability and enlarged motor unit size. In contrast, anti-MAG neuropathy patients demonstrated a proximal pattern of nerve enlargement and an axonal excitability profile characterised by reduced super-excitability consistent with increased juxta-paranodal fast potassium channel conductance. Conclusion: Patterns of nerve enlargement and neurophysiological profiles differ in the immune-mediated neuropathies providing insights into molecular mechanisms. These results provide templates that can guide treatment approaches. The combination of directed autoantibody assays and measures of axonal function can be used to monitor disease progression and therapeutic response.